1977
DOI: 10.1111/j.1365-2265.1977.tb02016.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3 Hour Metyrapone Test in Children and Adolescents

Abstract: An evaluation of a new 3 h metyrapone test is presented. The test consists of one oral dose of metyrapone given at 08.00-09.00 hours, and determination of plasma deoxycortisol from a single capillary blood sample taken 3 h later. The test has been assessed in children and adolescents in conjunction with a 5 day metyrapone test, insulin test, vasopressin test, and ACTH test in forty-five reference subjects, in thirty-six hypopituitary subjects with normal or deficient ACTH secretion, in three subjects with prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0
1

Year Published

1977
1977
1993
1993

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Metyrapone tests have been developed in which levels of 11-deoxycortisol are used as criteria for normal pituitary-adrenal response (Spark 1971;Jubiz et al 1970b;Leisti 1977). These tests involve different time schedules for metyrapone admini¬ stration: 6 daily doses (Spark 1971), one large dose (2-3 g) at midnight (Jubiz et al 1970b), or one dose at 08.00 h (Leisti 1977).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metyrapone tests have been developed in which levels of 11-deoxycortisol are used as criteria for normal pituitary-adrenal response (Spark 1971;Jubiz et al 1970b;Leisti 1977). These tests involve different time schedules for metyrapone admini¬ stration: 6 daily doses (Spark 1971), one large dose (2-3 g) at midnight (Jubiz et al 1970b), or one dose at 08.00 h (Leisti 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Measuring plasma 11-deoxycortisol level at 08.00 h, rather than 24-h urine collection (Spark 1971), shortens the test to 24 h and simplifies it considerably. Different one-dose metyrapone test conducted at various times of the day (Jubiz et al 1970b; Leisti 1977) have been suggested, but have not been widely accepted since they do not necessarily show stimulation of adrenal corticosteroid production, but rather blockade of cortisol formation from 11-deoxycortisol, as total 17-OHCS levels are not shown to rise (Liddle 1981).…”
mentioning
confidence: 98%
“…The increase of S in plasma is accompanied by an augmented urinary excretion of tetrahydro-11-deoxycortisol (H4S). Short metyrapone tests (usually consisting of one dose of metyrapone) have been described (Jubiz et al 1970b;Zachmann et al 1974;Blichert-Toft 1975;Leisti 1977), but the conventional oral mety¬ rapone test is still widely used.Oral administration of metyrapone for three consecutive days results in a 95% inhibition of the 11-ß-hydroxylase, at a daily dose of 4.5 g (Cope et al 1966).The relative increase of urinary H4S after mety¬ rapone administration exceeds the relative rise in plasma S considerably (Zachmann et al 1974). …”
mentioning
confidence: 99%
“…The increase of S in plasma is accompanied by an augmented urinary excretion of tetrahydro-11-deoxycortisol (H4S). Short metyrapone tests (usually consisting of one dose of metyrapone) have been described (Jubiz et al 1970b;Zachmann et al 1974;Blichert-Toft 1975;Leisti 1977), but the conventional oral mety¬ rapone test is still widely used.…”
mentioning
confidence: 99%
“…Though shorter metyrapone tests have been suggested (24,31,41,46) the conventional oral metyrapone test probably continues to be the most widely used test of the hypothalamo-pituitary system. Yet, its interpretation has re mained problematic.…”
Section: Discussionmentioning
confidence: 99%